Survival outcomes in trial defined high-risk hormone receptor-positive/human epidermal growth factor receptor II-negative early breast cancer: impact of adjuvant chemotherapy - Ta-Chung Chao; Deanna Gracia; Chan-Heng Ho; Hao-Yang Chen; Chi-Cheng Huang; Ling-Ming Tseng (Discover Oncology)
Abstract Background Clinical trials have shown the efficacy of adding CDK4/6 inhibitors to standard endocrine therapy in hormone receptor (HR)-positive, human epidermal growth factor receptor II (HER2)-negative high-risk early breast cancer. Materials and methods HR+ /HER2− early breast cancers were retrieved from cancer registry. The primary endpoints were overall survival (OS) and recurrence-free survival (RFS) among trial-defined high-risk patients, as well as the impact of adjuvant chemotherapy. Results Among 2758 registered cases, 511 and 1207 patients met MonarchE (M) and NATALEE (N) high-risk criteria, respectively. OS was 94.8% for M-high/N-high, 96.8% for M-low/N-high, 90.7% for M-high/N-low, and 98.9% for M-low/N-low patients, with a hazard ratio (HR) of 2.3 and 2.8 for M-high and N-high, respectively. For RFS, chemotherapy reduced recurrence risk in M-high patients (HR: 0.24) but showed no benefit for N-high patients overall, except for stage III N-high cases (HR: 0.2). Conclusion Adjuvant chemotherapy significantly reduced recurrence risk in M-high patients with early breast cancer. Further stratification of M-low/N-high patients is needed to guide tailored chemotherapy approaches alongside CDK4/6 inhibition.